EVALUASI MANAJEMEN PELAYANAN PUBLIK - Febri Yuliani, Arliliwati, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Evaluation of Public Service Management. The approach or type of research is qualitative. This study aims to determine how the public service management of PDAM Tirta Siak. Research informants are directors, staff of human resources, subscription relationships, transmission and customers. Data collection techniques are interviews, observation and documentation. Data analysis starts from data reduction, classification and drawing conclusions. The results of this study found that the public service management of PDAM Tirta Siak Pekanbaru City was not carried out optimally.